First we want to cross multiply. 5 * 6 = 3c * 1
Then simplify it down and multiply 5 * 6
30 = 3c * 1
Now re-order the terms so we have an easier time multiplying!
30 = 3 * 1c
Multiply 3 by 1
30 = 3c
Now we want to solve for the variable c so we want to move all terms that have c to the left and all other terms to the right.
Lets start by adding -3c to each side of the equation.
30 + -3c = 3c + -3c
Combine our like terms...
30 + -3c = 0
Now add -30 to each side of the equation
30 + -30 + -3c = 0 + -30
Combine like terms again.
0 + -3c = 0 + -30
-3c = 0 + -30
Like terms.
-3c = -30
Now simply divide both sides by -3.
-3c/3 = -30/-3
This gives us 10. Therefore c = 10.